30 years after the fall of the Berlin Wall: Regional health differences in Germany - Thomas Lampert; Stephan Müters; Benjamin Kuntz; Stefan Dahm; Enno Nowossadeck (Journal of Health Monitoring, 2019)
Following the fall of the Berlin Wall in November 1989, considerable effort was made to bring the living conditions and levels of social participation in the former East German federal states into line with the former West German federal states. As a result, differences in health between the East and the West diminished significantly, in many cases as early as the 1990s, examples being life expectancy and cardiovascular mortality. In regard to health behaviour, the overall tendency has also clearly been one of convergence. Thus, only very small differences can be observed today, for example in the use of tobacco or in the prevalence of obesity. Yet the results also highlight the insufficiency of regarding the remaining differences as a simple comparison between East and West. Instead, the focus should shift towards smaller-scale approaches that take regional differences in living conditions into account.